Enantioselective synthesis of chiral carbocyclic pyrimidine nucleosides via asymmetric cyclopropanation. Issue 43 (24th October 2019) - Wang, Hai-Xia; Li, Wen-Peng; Xia, Chao; Xie, Ming-Sheng; Qu, Gui-Rong; Guo, Hai-Ming
Graphical abstract: Highlights: Chiral cyclopropyl pyrimidine carbocyclic nucleoside bearing a quaternary center. Organocatalytic asymmetric Michael-initiated cyclopropanation. Cyclopropyl pyrimidine carbocyclic nucleoside with axis chirality phenomenon. Abstract: An efficient method to construct chiral cyclopropyl pyrimidine carbocyclic nucleoside analogues bearing a quaternary center was developed via asymmetric Michael-initiated cyclopropanation. The axis chirality was observed in cyclopropyl pyrimidine carbocyclic nucleoside analogues for the first time, which was caused by the rotationally restricted NC bond in N -COPh moiety. Using (DHQD)2 AQN as the organocatalyst, diverse cyclopropyl pyrimidine carbocyclic nucleoside analogues were generated in 76–93% yields and 73–96% ee.